2016
DOI: 10.1002/anie.201604305
|View full text |Cite
|
Sign up to set email alerts
|

Trapping Aluminum Hydroxide Clusters with Trisilanols during Speciation in Aluminum(III)–Water Systems: Reproducible, Large Scale Access to Molecular Aluminate Models

Abstract: To gain molecular level insights into the properties of certain functions and units of extended oxides/hydroxides, suitable molecular model compounds are needed. As an attractive route to access such compounds the trapping of early intermediates during the hydrolysis of suitable precursor compounds with the aid of stabilizing ligands is conceivable, which was tested for the aluminum(III)/water system. Indeed, trisilanols proved suitable trapping reagents: their presence during the hydrolysis of Al(i) Bu2 H in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 57 publications
2
49
0
1
Order By: Relevance
“…[106] Lokare et al have predicted that the acidity of the Al-O(H)-Al entitiesi sl ower than that of the Si-O(H)-Al units in zeolites but highert han that of at erminal SiÀOH or AlÀOH group. [111] To characterize the acidic nature of the -OH species in more detail, these studies were subsequently extended to include gas-phase clusters. [107] Information on the unperturbed bridging Al-O(H)-Al groups can be obtainedb yr emoving the three THF molecules from 1.C alculations predict that the diprotonation energy of this species is similar to that in the proton forms of well-known zeolite catalysts.…”
Section: Understanding the Reactivity Of An Active Sitementioning
confidence: 99%
“…[106] Lokare et al have predicted that the acidity of the Al-O(H)-Al entitiesi sl ower than that of the Si-O(H)-Al units in zeolites but highert han that of at erminal SiÀOH or AlÀOH group. [111] To characterize the acidic nature of the -OH species in more detail, these studies were subsequently extended to include gas-phase clusters. [107] Information on the unperturbed bridging Al-O(H)-Al groups can be obtainedb yr emoving the three THF molecules from 1.C alculations predict that the diprotonation energy of this species is similar to that in the proton forms of well-known zeolite catalysts.…”
Section: Understanding the Reactivity Of An Active Sitementioning
confidence: 99%
“…[2c] Deprotonation of the bridging aluminum hydroxyl groups is possible on using amine bases. More recently, Limberg et al reported the synthesis of [Al 3 (μ 2 -OH) 3 (THF) 3 {PhSi(OSiPh 2 O) 3 }] which is characterized by three OH-linked tetrahedral coordinated aluminum atoms in its core. [3] The hydrolysis of both compounds led to larger clusters with a core featuring octahedral coordinated aluminum atoms, which are linked by bridging hydroxide ligands.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Limberg et al reported the synthesis of [Al 3 (μ 2 -OH) 3 (THF) 3 {PhSi(OSiPh 2 O) 3 }] which is characterized by three OH-linked tetrahedral coordinated aluminum atoms in its core. [3] The hydrolysis of both compounds led to larger clusters with a core featuring octahedral coordinated aluminum atoms, which are linked by bridging hydroxide ligands. Barron et al reported on the synthesis of the cluster [Al 10 (OH) 16 (OSiEt 3 ) 14 ] that shows a motif which resembles moieties found in boehmite or diaspore.…”
Section: Introductionmentioning
confidence: 99%
“…Aqueous aluminum chemistry displays ar ich array of oxohydroxo clusters,a se xemplified by flat-Al 13 [Al 13 (OH) 24 -(H 2 O) 24 ] 15+ , [1,2] isomers of the Al 13 -keggin ion [Al 13 O 4 (OH) 24 -(H 2 O) 12 ] 7+ , [3,4] and larger clusters like the Al 30 cation [Al 30 O 8 -(OH) 56 (H 2 O) 26 ] 18+ . [5,6] Although researchers have explored this chemistry for more than acentury,novel species continue to emerge.I n2 005, [7] Casey and co-workers reported the octameric aluminum hydroxide cluster Al 8 (OH) 14 (H 2 O) 18 -(SO) 5 (Al 8 ), which was isolated during the attempted synthesis of the aluminum sulfate dimer Al 2 (OH) 2 (H 2 O) 8 (SO 4…”
mentioning
confidence: 99%
“…[7] This long time raises questions about whether the cluster may be readily synthesized and whether it even exists in solution. A2 016 report [8] describes an additional example of an Al 8 cluster;i nt his case,t he cluster was isolated from an organic solvent and stabilized with trisilanol capping ligands.…”
mentioning
confidence: 99%